Glycosylation, denaturation, and aggregation of soy proteins in defatted soy flakes flour: Influence of thermal and homogenization treatments - Ingrassia, Romina (2016)
This paper provides a systematic study of the impact of different thermal treatments (62 ± 2°C, without and with relative humidity control, 79%) on soy protein in defatted soy flour and their aqueous dispersions. The effect of dispersing treatments (magnetic stirring, high-speed and highpressurehomogenization) on dispersions also was assessed. Changes in protein solubility (water and 0.2 g KOH/100 g solution), apparent-reactive lysine content, urease and trypsin inhibitor activities, protein denaturation and FTIR spectra were studied. Glycosylation, aggregation and denaturation of storage and biologically active soy proteins were observed in different degree, being mainly promoted by the control of relative humidity and dispersibility of the sample.